Pengaruh Transformational Leadership dan Motivation terhadap Employee Performance (Studi Kasus pada PT Glostar Indonesia 1 Cikembar) - Fikri Irawan Abdurahman; Imam Septiana (Institut Manajemen Wiyata Indonesia, 2018)
This study aims to know and analyze the Transformational Leadership, Motivation and Employee Performance at PT. Glostar Indonesia, this research was conducted in QIP department (quality integration program), We taking a sample of 158 employees, research methods conducted by collecting data documentation and questionnaires, descriptive analysis method, classical assumption test, and hypothesis test using SPSS 18. The results of research calculations obtained by the influence of transformational leadership style on employee performance has t arithmetic of 4,266 with a significance of 0.000. Thus the transformational leadership style has a significant positive effect, it indicates that the better the transformational leadership style in an organization or company the better the performance of employees in the company. The influence of motivation on employee performance has t arithmetic equal to 10,871 with signification 0.000. Thus the motivation has a significant positive effect, this indicates that the better the company's motivation the better the performance of employees in the company. The influence of transformational leadership style and motivation simultaneously on employee performance reached F count of 66.999 with 0.000 significance, the result of coefficient of determination (R²) transformational leadership style and motivation influence to performance equal to 45,7%